Symposium 3: Supporting the “Digital Natives”: What is the role of schools? - Eynon, Rebecca (Proceedings of the International Conference on Networked Learning, 2010)
The notion of the “digital native” has become pervasive in popular discourse about young people and new technologies. In this discourse, parents and teachers (“the digital immigrants”) have been characterised as unable to support young people in their uses of the Internet and other new technologies because (unlike the digital natives) the immigrants were not born into a world surrounded by new technologies. Yet in contrast, empirical research has shown that there is limited empirical basis for a distinction in the ways that people use new technologies because of when they were born and that young people are not all the same – they engage with new technologies in a variety of ways and vary considerably in their skills to use new technologies. Given this empirical evidence, it is important to better understand why and in what ways young people use computers and the Internet and if and how they need to be supported in this use. This paper aims to add to existing research by using empirical survey data on how and why young people in Britain use the Internet outside formal educational settings. The data is based on a nationally representative face to face survey of 1000 young people in Britain aged 8, 12, 14 and 17-19. The survey was conducted between December 2008 and January 2009 utilising a stratified sampling strategy. The survey forms part of the Learner and their Context study, commissioned by Becta, which explores young people’s views and experiences of new technologies outside school and is designed to inform the next phase of the UK’s Harnessing Technology Strategy. This paper will provide an overview of the ways young people are using the Internet for a range of activities (e.g. for homework, information seeking and creating content) and examine the factors that help to explain why young people are using new technologies for these purposes. The results demonstrate that there are a range of individual and contextual factors that help to understand use of the Internet and that formal contexts of education have an important role to play in supporting the “digital natives”.